Higher-order simulations of interactional aerodynamics on full helicopter configurations using a Hamiltonian strand approach - Petermann, J.; Jung, Y.S.; Baeder, J.D.; Rauleder, J. (My University, 2018)
Time-accurate numerical predictions of the interactional aerodynamics between NASA's generic ROBIN fuselage and its four-bladed rotor were performed using the recently developed RANS solver HAMSTR. The fifth-order WENO reconstruction scheme, the third-order MUSCL scheme, a secondorder temporal resolution, and the Spalart-Allmaras turbulence model were used. Three-dimensional volume meshes were created in a robust manner from two-dimensional unstructured surface grids using Hamiltonian paths and strands on nearbody domains. Grid connectivity was established between nearbody and background domains in an overset fashion. Two previously researched operational conditions were reproduced, i.e., a near-hover case and a medium-speed forward flight case at an advance ratio of μ = 0:151. The results were compared with various experimental and numerical references and were found to be in good agreement with both. The comparison included the analysis of the rotor wake structure, tip vortex trajectories and strength, steady and dynamic fuselage pressure distributions in longitudinal and lateral directions, and rotor inflow predictions